O JOGO do DIÁLOGO: ALGUMAS INDAGAÇÕES SOBRE A RELAÇÃO ENTRE AUTOR, OBRA E ESPECTADOR - Jacqueline Kelly Prado de Souza (2006)
Starting from the contact with the works of Waltercio Caldas, and from the observation of their peculiar aesthetic shock, some questions about the relationship between spectator and artwork appeared. The conductor threads of these questionings are the interpretation and the perception of the artistic object. For this reason, the research had its beginning in the field of the Neuroscience, at the universe of feelings and self-perception, where the singularity of each perception from each spectator on the artistic object was investigated. It was necessary an approach over the desires, the interests, the looking on the artwork by the spectator. The thoughts from Didi-Huberman about the nature of the art object and the different attitudes and looking ways that the spectator can deal with the works were essential, as so as the thoughts from Barthes about the relationship between author, spectator and artwork, and the thoughts from Arnheim concerning intuition and intellect in the apprehension of the work of art. Related to the artwork, the ideas of the theoretician Um berto Eco were used, specifically the texts concerning the interpretation, super interpretation and the purpose of the artwork, and also the interpretation of artwork according to the analysis of Martine J oly. In the last chapter I present personal readings of some works of Waltercio Caldas, where I relate the production of the chosen artist with the utilized theoretical referential.